Family and household religion : toward a synthesis of Old Testament studies, archaeology, epigraphy, and cultural studies - Albertz, Rainer, 1943- (Eisenbrauns, 2014)
"This is the most recent collective contribution of a group of biblical scholars and archaeologists who are engaged in an ongoing debate about the nature of family and household religion in ancient Israel and its environment. It is intended to complement the volume Household and Family Religion in Antiquity, edited by John Bodel and Saul M. Olyan (Bodel and Olyan 2008), which grew out of a conference held at Brown University in 2005 on household and family religion in the ancient Mediterranean world, with an emphasis on cross-cultural comparison. After the conference at Brown, there was a session held at the meeting of the European Association of Biblical Studies in Budapest in 2006 in which the focus was narrowed to the gender dimensions of Israelite family/household religion. Two more sessions focusing on the Israelite house as a locus of family religion took place at the European Association of Biblical Studies meeting in Vienna in 2007. A fourth meeting at Westfaelische Wilhelms-Universitaet Muenster in April 2009 emphasized theoretical and methodological challenges facing scholars of household and family religion (e.g., the conceptualization of family/household religion, the problem of identifying pertinent artifacts, and the difficulties inherent in using texts together with material evidence). This volume is a direct outgrowth of the Muenster meeting"--